Sunset empire : a morris baker mystery - Weiss, Josh (New York : Grand Central Publishing, 2023)
"December, 1959: The Korean War rages on. Protesting the bloody conflict, a Korean-American man by the name of William Yang suddenly blows himself up in the middle of a Los Angeles department store just before Christmas, which leads the U.S. government to reopen the internment camps used during World War II. President Joseph McCarthy's America has never been more on edge, paranoid, and above all, dangerous. Several weeks later, a woman hires Morris Baker, now working as a private investigator, to track down her missing husband - Henry Kissinger - who may have a shadowy connection to Yang's purported terrorist attack. The ensuing investigation for the missing State Department consultant working for Vice President Richard Nixon sends Baker on another thrilling adventure of deceit, intrigue, sex, murder, and conspiracy where the safety of the entire world may hang in the balance"--
Keywords: Private investigators -- Fiction; Missing persons -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Alternative histories (Fiction)